Practicing Sustainability - Madhavan, Guru; Oakley, Barbara; Green, David; Koon, David; Low, Penny (Springer New York : Imprint: Springer, 2013)
"Delightful...the chapters are gems of precision and insight."-Michael Spence, Nobel Prize Winner in Economics Sustainability applies to everybody. But everybody applies it differently, by defining and shaping it differently-much as water is edged and shaped by its container. It is conceived in absolute terms but underpinned by a great diversity of relatively "green"-and sometimes contradictory-practices that can each make society only more or less sustainable. In Practicing Sustainability, chefs, poets, music directors, evangelical pastors, skyscraper architects, artists, filmmakers, as well as scientific leaders, entrepreneurs, educators, business executives, policy makers, and the contrarians, shed light on our understanding of sustainability and the role that each of us can play. Each contributor addresses what sustainability means, what is most appealing about the concept, and what they would like to change to improve the perception and practice of sustainability. What emerges from their essays is a wide spectrum of views that confirm an important insight: Sustainability is pursued in different ways not only due to different interpretations, but also because of varying incentives, trade-offs, and altruistic motives. Practicing and achieving sustainability starts with a willingness to look critically at the concept. It also means enabling rich and vigorous discussion based on pragmatism and common sense to determine a framework for best ideas and practices. With time and the much needed critical thinking, sustainable development will become a more integral part of our culture. By sharing experiences and crisp insights from today's savants, Practicing Sustainability serves as a stepping stone to the future.